Subcutaneous panniculitis-like T-cell lymphoma: A clinicopathologic study of 5 cases - Sameer Bakhshi; Prasenjit Das; Kriti Puri; Mayank Singhal; M Ramam; Atul Sharma; Venkateshwaran K Iyer; Siddhartha Datta Gupta (Wolters Kluwer Medknow Publications, 2011)
Background: Subcutaneous panniculitis-like T-cell lymphoma is as yet a poorly characterized subtype of cutaneous T-cell lymphomas. It is difficult to diagnose and lacks a standard treatment protocol. Materials and Methods: We report our experience with five such cases in patients with age ranging from 13 to 45 years, wherein we reviewed their clinical presentations, histopathological findings, treatment and clinical outcome. Results: Three out of the five cases are alive of which two are in complete remission. Our series stresses on the need to be aware of this uncommon entity in a dermatology clinic. Facial and upper extremity skin nodules with involvement of the lower dermis on light microscopical examination and suggestive immunohistochemical findings were frequently observed in our patients in contrast to previously described cases.